PENGEMBANGAN APLIKASI ANDROID BERUPA ROLE PLAYING GAME PADA POKOK BAHASAN GERAK LURUS DI SMA - Muhammad Hafidz; Vina Serevina; Handjoko Permana (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
The aim of this research was to develop learning media of motion in one dimension to increase analysis capability of students. This research is motivated from student’s behavior pattern using their gadget, first data form initial preliminary questionnaire given by senior high school students and observation in class about propensity of students to learn with technology development. This research was done in school at even semester on 2014-2015, media which was developed form android application made until being learning media works effectively and efficiently where students can learn motion in one dimension anywhere and anytime by their gadget. Method of this research is Research and Development (R&D) by Borg and Gall and also development design by ASSURE. Research steps were done still until product trials. Collecting validation data of learning media using instrument form questionnaire to media and objectives master. Based on research is expected development of learning media, students can understand motion in one dimension easier and can be accessible anytime and anywhere. Key: Learning media development, Motion in one dimension, Android application.